2019
DOI: 10.3390/ijerph16091624
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Amendment Reduces Soil Cd Availability and Cd Uptake of Two Pennisetum Species

Abstract: Silicon (Si) plays important roles in alleviating heavy metal stress, but the migrating effects and mechanisms, especially for Pennisetum, are not well studied. In this study, Pennisetum glaucum and Pennisetum glaucum × P. purpureum were used to explore the impacts of Si application on alleviating cadmium (Cd) toxicity and its possible mechanism. Treatments consist of four levels of Cd (0, 10, 50, and 100 mg·kg−1) with or without 2.0 mM Si amendments. Under Cd stress, Si application significantly increased pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 66 publications
(86 reference statements)
3
22
1
1
Order By: Relevance
“…Cadmium has high assimilability and mobility; thus, its entry into plants is possible through the roots, and it is translocated to shoots in an ionic form in the xylem and phloem over transporters and transpiration [2]. Cadmium can enter the xylem via symplastic transport and possibly through apoplastic transport under high exposure [37].…”
Section: Cadmium Entry Into Shoots and Grainsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cadmium has high assimilability and mobility; thus, its entry into plants is possible through the roots, and it is translocated to shoots in an ionic form in the xylem and phloem over transporters and transpiration [2]. Cadmium can enter the xylem via symplastic transport and possibly through apoplastic transport under high exposure [37].…”
Section: Cadmium Entry Into Shoots and Grainsmentioning
confidence: 99%
“…The Si can enhance seedling biomass and reduce metal concentration in the shoots and roots of plant seedlings and the xylem sap flow [77]. Dong et al [2] reported that Si utilization remarkably decreases available/oxidizable Cd in soil at 50 and 100 mg/Kg Cd levels. Naeem et al [78] reported that Si application might reduce the Cd contents in wheat by 28%.…”
Section: Using Simentioning
confidence: 99%
See 2 more Smart Citations
“…Another group of researchers who used Si as root application reported that Si in root application could alleviate heavy metal (HM) stress more efficiently than Si foliar-application due to (1) decreased HM absorption from roots to shoots (Dong et al 2019), (2) enhanced HM binding with root cell walls and delimited their apoplastic transport (Huang et al 2018), and (3) coprecipitate with HMs to minimize biological active HM concentration in soil (Lu et al 2017).…”
Section: Introductionmentioning
confidence: 99%